ANALISIS KESIAPSIAGAAN PERAWAT DALAM MEMBERIKAN PELAYANAN KEGAWATDARURATAN SISTEM PERNAFASAN AKIBAT BENCANA ALAM DI WILAYAH KERJA DINAS KESEHATAN KABUPATEN DELI SERDANG - Nagoklan Simbolon; Paska Situmorang (Elisabeth Health Jurnal, 2017)
Preparedness and complete alertness is one of the important elements of activities in reducing the risk and the impact of disaster. The same is true to nurses’ preparedness and complete alertness in providing emergency service in respiratory system which is urgently needed during the disaster immediate responsiveness. Quick and accurate service can help and save victims from physical defect and death Goal: The objective of the research was to know the condition of nurses’ preparedness and complete alertness in providing emergency service in respiratory system, based on the their knowledge, attitude, and skills. Methods: The research method is The research used a descriptive qualitative survey. The population was all 40 nurses who were involved in disaster response team in four Puskesmas working areas of the Health Office in Aceh Tamiang District: Kejuruan Muda Puskesmas, Karang Baru Puskesmas, Kota Kuala Simpang Puskesmas, and Bandar Pusaka Puskemas Result : The result of the research showed that 65% of the respondents had good knowledge, 82.5% of them had positive attitude, 55.0% of them were skillful in conducting the acting procedure of Heimlich maneuver, , and skillful in Lung-Heart Restitution was less Conclusion: The conclusion and the important implication in this research could that the education and the training of Basic Life Support and Basic Traumatic Coronary Life Support highly supported nurses’ alertness in providing emergency service in respiratory system.